2020
DOI: 10.1038/s41598-020-66080-z
|View full text |Cite
|
Sign up to set email alerts
|

Infection by cyst nematodes induces rapid remodelling of developing xylem vessels in wheat roots

Abstract: cyst nematodes induce host-plant root cells to form syncytia from which the nematodes feed. comprehensive histological investigation of these feeding sites is complicated by their variable shape and their positions deep within root tissue. Using tissue clearing and confocal microscopy, we examined thick (up to 150 μm) sections of wheat roots infected by cereal cyst nematodes (Heterodera avenae). This approach provided clear views of feeding sites and surrounding tissues, with resolution sufficient to reveal sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Our data showed that adventitious lateral roots nonetheless support syncytium hypertrophy and female growth. This is in line with a previous hypothesis that adventitious lateral roots may increase water influx towards nematode syncytia (Levin et al ., 2020). However, the positive correlation between the number of adventitious lateral roots and syncytium and female size was disrupted in the repressor 35S::WOX11-SRDX and in the lbd16-2 mutants.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data showed that adventitious lateral roots nonetheless support syncytium hypertrophy and female growth. This is in line with a previous hypothesis that adventitious lateral roots may increase water influx towards nematode syncytia (Levin et al ., 2020). However, the positive correlation between the number of adventitious lateral roots and syncytium and female size was disrupted in the repressor 35S::WOX11-SRDX and in the lbd16-2 mutants.…”
Section: Discussionsupporting
confidence: 93%
“…The effect of WOX11 on syncytium hypertrophy and female fecundity is not causally linked to adventitious lateral root formation WOX11-adventitious lateral roots emerge in proximity or adjacent to nematode syncytia (Golinowski et al, 1996, Willig et al, 2023. As adventitious lateral roots are both strong sinks of assimilates (Stitz et al, 2023) and an additional source of water and minerals (Levin et al, 2020), we hypothesized that they could either compete or support syncytium hypertrophy and nematode fecundity. To test this, we counted the number of adventitious lateral roots emerging from 28 dpi syncytia in Col-0, 35S::WOX11-SRDX, and lbd16-2 and performed a correlation analysis with female and syncytium size.…”
Section: Wox11 Attenuates Nematode Female Fecundity In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…WOX11-mediated adventitious rooting may contribute to tolerance of Arabidopsis to biotic stress by restoring the capacity of the root system to take up and transport water and minerals. Cyst nematodes modify host cells within the vascular cylinder into a permanent feeding structure, which interrupts the continuity of surrounding xylem vessels (Golinowski et al, 1996;Sobczak et al, 1997;Levin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As such, there is a potential role for IBA in feeding cell development, because lateral root formation and feeding cell development share similar developmental processes (Cabrera et al, 2015a). Infection of M. incognita as well as other RKNs and CNs lead to spontaneous secondary root formation originating from the feeding site to which auxins seems to contribute (Olmo et al, 2017;Levin et al, 2020). Whereas a role of auxin in CN and RKN parasitism has been widely accepted, this is not the case for PPNs with a migratory lifestyle.…”
Section: Auxins At Nematode Feeding Sitesmentioning
confidence: 99%